An investigation on the effects of supply chain management on improvement of firms’ financial performance - Mohammad Mokhtari; Abutorab Alirezaie (Management Science Letters)
Supply chain management plays essential role on improvement of the efficiency of production systems. It helps firms meet their expectations, deliver their products on time and build a good brand. This paper performs an empirical investigation to study the effect of good relationships among various suppliers on financial figures in an Iranian automaker. The proposed study investigates the effects of seven variables including communication, cooperation, commitment, compatibility, organization climate, dependency and trust on two financial figures including return on assets and return on equities. Using structural equation modeling, the study detects that communication, dependency and trust influence positively on return on assets. In addition, communication, cooperation, trust and commitment have positive impact on return on equities.